2018
DOI: 10.1038/s41598-018-22228-6
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial drug discovery using Mycobacteria-infected amoebae identifies anti-infectives and new molecular targets

Abstract: Tuberculosis remains a serious threat to human health world-wide, and improved efficiency of medical treatment requires a better understanding of the pathogenesis and the discovery of new drugs. In the present study, we performed a whole-cell based screen in order to complete the characterization of 168 compounds from the GlaxoSmithKline TB-set. We have established and utilized novel previously unexplored host-model systems to characterize the GSK compounds, i.e. the amoeboid organisms D. discoideum and A. cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 65 publications
(84 reference statements)
2
27
0
1
Order By: Relevance
“…The diamines and indolcarboxamides have already entered clinical trials or preclinical studies (Rao et al, 2013;World Health Organization, 2018). The current literature suggest they all target MmpL3 since the resistant mutations have been specifically mapped to the mmpL3 gene Grzegorzewicz et al, 2012;Ioerger et al, 2013;Kozikowski et al, 2017;La Rosa et al, 2012;Lun et al, 2013;McNeil et al, 2017;Rao et al, 2013;Rayasam, 2014;Stanley et al, 2012;Tahlan et al, 2012;Trofimov et al, 2018;Zheng et al, 2018). Since our structural data are only for four MmpL3 inhibitors, we investigated if molecular docking could indicate how six other putative MmpL3 inhibitors might bind to this protein.…”
Section: Discussionmentioning
confidence: 99%
“…The diamines and indolcarboxamides have already entered clinical trials or preclinical studies (Rao et al, 2013;World Health Organization, 2018). The current literature suggest they all target MmpL3 since the resistant mutations have been specifically mapped to the mmpL3 gene Grzegorzewicz et al, 2012;Ioerger et al, 2013;Kozikowski et al, 2017;La Rosa et al, 2012;Lun et al, 2013;McNeil et al, 2017;Rao et al, 2013;Rayasam, 2014;Stanley et al, 2012;Tahlan et al, 2012;Trofimov et al, 2018;Zheng et al, 2018). Since our structural data are only for four MmpL3 inhibitors, we investigated if molecular docking could indicate how six other putative MmpL3 inhibitors might bind to this protein.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, identification of infection enhancers in the set of compounds was quite surprising, although the same observation was already reported in the phenotypic screen of the GlaxoSmithKlyne TB-set of anti-mycobacterial antibiotics in the A. castellanii-M. marinum model of infection (Trofimov et al 2018). Notably here, five compounds were identified that increased at least 2-fold the intracellular M. marinum bacterial load (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…To evaluate the effect of hit compounds on host fitness, we used D. discoideum cells expressing GFP-ABD to measure toxic and growth inhibitory activities of compounds (Trofimov et al 2018). In parallel, a cell viability test using Alamar blue was performed using A. castellanii 4 hours after hit compound addition at a 30μM concentration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations